2018
DOI: 10.1007/s11130-018-0668-z
|View full text |Cite
|
Sign up to set email alerts
|

Peptides from Chia Present Antibacterial Activity and Inhibit Cholesterol Synthesis

Abstract: In previous studies, it has not been reported that protein isolated from chia interferes favorably with antibacterial activity, and reduces cholesterol synthesis. The objective of this study was to determine whether commonly used commercial microbial proteases can be utilized to generate chia protein-based antibacterial and hypocholesterolemic hydrolysates/peptides, considering the effects of protein extraction method. Alcalase, Flavourzyme and sequential Alcalase-Flavourzyme were used to produce hydrolysates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…The consumption of chia seed has shown promise for reducing the levels of serum cholesterol, since it has high concentrations of dietary fiber and unsaturated omega‐3 fatty acids (da Silva et al., ). Most recently, it has been demonstrated that chia proteins and chia bioactive peptides can block key markers of cholesterol synthesis, such as 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase (HMG‐CoA reductase) (Coelho et al., ).…”
Section: Benefits Of Chia Seedsmentioning
confidence: 99%
See 2 more Smart Citations
“…The consumption of chia seed has shown promise for reducing the levels of serum cholesterol, since it has high concentrations of dietary fiber and unsaturated omega‐3 fatty acids (da Silva et al., ). Most recently, it has been demonstrated that chia proteins and chia bioactive peptides can block key markers of cholesterol synthesis, such as 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase (HMG‐CoA reductase) (Coelho et al., ).…”
Section: Benefits Of Chia Seedsmentioning
confidence: 99%
“…The number of studies using isolated peptides from chia are limited but show beneficial promising health effects. A protein hydrolysate from chia seed, produced by enzymatic hydrolysis, with alcalase and/or Flavourzyme, demonstrated antibacterial activity, reducing the velocity of enzymatic reaction of and 3‐hydroxy‐3‐methylglutaryl coenzyme A reductase (HMG‐CoA reductase) (Coelho et al., ). The chia protein hydrolysate has also shown ACE‐inhibitory and antioxidant activities (Chim‐Chi, Gallegos‐Tintoré, Jiménez‐Martínez, Dávila‐Ortiz, & Chel‐Guerrero, ; Segura Campos et al., ; Segura‐Campos et al., ).…”
Section: Analysis Of Bioactive Peptides From Chia Seed Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of peptides derived from chia protein have been demonstrated by biochemical indicators. They include inhibition of ACE (angiotensin‐converting enzyme), antioxidant capacity, antibacterial properties, and anti‐cholesterolemic effects, but there are not studies of the effects of chia peptides at the cellular level.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the hypocholesterolemic activity of peptides is owing to direct bile acid and neutral sterol binding in the intestine. Bioactive peptides extracted from chia seeds have been shown to have hypocholesterolemic function by inhibiting cholesterol homeostasis [ 143 ]. Furthermore, it has been documented that hydrophobic bioactive peptides containing leucine, tryptophan, and tyrosine have better hypocholesterolemic activity [ 144 ].…”
Section: Physiological Properties Of Food-derived Bioactive Peptidesmentioning
confidence: 99%